What Influences Tourist’ Visit Decision to Coastal Area? A Lesson Learned from Southern Beaches of West Java - Kijima, Kyoichi; Novani, Santi; Widiana, Retno; Palumian, Yonathan; Cintyawati, Cici (The Asian Journal of Technology Management (AJTM), 2020)
Abstract. Indonesia, as an archipelago country, posits the third rank of the world’s longest coastline list. The potential of coastal tourism was voluminous to be developed in the future. Since the tourism contribution has a positive inclination during the years to GDP, the government put the tourism as one of the national development priority sector. However, the circumstances were not well-ready. Still, the beaches were not gaining substantial attention from the tourist for several areas even though it has a scenic view. The current study aims to analyze factors influencing tourist decision to choose the coastal area that may lead to tourism development in Southern Beaches of West Java. It is the most populated area and has many potential beaches. Methods used in this paper were mixed methods using a qualitative and quantitative approach. First, exploratory is conducted by interviews and analyzed manually by transcribed and coded to define what variables explored. Then, Exploratory factor analysis (EFA) was done to examine the factors of influences tourist’ visit decision. The result demonstrates five factors are influencing the tourist decision to choose the Southern Beach tourism in West Java, i.e., hotel and restaurant, word of mouth testimony, access, convenience (cost and food attraction) and local attribution.Keywords: Coastal tourism, tourist decision, mixed method, exploratory, exploratory factor analysis